SHORT BOWEL SYNDROME AND INTESTINAL FAILURE IN ADULTS: ANATOMY-DRIVEN PHENOTYPES, ADAPTATION BIOLOGY, AND CONTEMPORARY INTESTINAL REHABILITATION - Stojanovic, Bojan; Milivojcevic Bevc, Ivana; Dimitrijevic Stojanovic, Milica; Colakovic, Goran; Stefanovic, Ivana; Stojanovic, Bojana; Tasic-Uros, Danijela (Halo 194 Scientific Journal of Emergency Medicine, 2026)
Short bowel syndrome (SBS) is the leading cause of chronic intestinal failure in adults and most commonly follows extensive small-bowel resection. The resulting loss of absorptive surface and regulatory feedback leads to a spectrum of malabsorption syndromes, ranging from compensated intestinal insufficiency to intestinal failure requiring long-term parenteral support. Clinical outcomes are determined less by residual length alone than by postoperative anatomy, particularly the presence of colon in continuity and preservation of distal ileum and the ileocecal region. The pathophysiology of SBS integrates reduced absorptive capacity, accelerated transit, gastric hypersecretion, disordered bile acid handling, microbiome perturbation, and impaired enteroendocrine signaling. Intestinal adaptation, driven by luminal nutrients and trophic hormones such as GLP-2, can partially restore function over months to years, enabling stepwise reduction of parenteral support in selected patients. Modern care is centered on structured intestinal rehabilitation delivered by multidisciplinary teams, combining individualized fluid–electrolyte strategy, optimized oral/enteral nutrition, targeted pharmacotherapy to control secretion and motility, prevention and management of catheter-related complications, and selective reconstructive surgery. Disease-modifying therapy with GLP-2 analogues can reduce parenteral support requirements in SBS-associated intestinal failure, while transplantation remains reserved for refractory, life-threatening complications. This review summarizes current concepts and evidence-based principles for diagnosis, phenotype stratification, rehabilitation, and long-term surveillance in adult SBS. Keywords: short bowel syndrome; chronic intestinal failure; home parenteral nutrition; colon in continuity; intestinal adaptation; teduglutide; high-output stoma.